2008
DOI: 10.2165/0126839-200809060-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Interaction between Nebicapone, a Novel Catechol-O-Methyltransferase Inhibitor, and Controlled-Release Levodopa/Carbidopa 200 mg/50 mg

Abstract: Following concomitant administration with levodopa/carbidopa CR 200 mg/50 mg, single doses of nebicapone 50 mg, 100 mg and 200 mg significantly and dose-dependently inhibited S-COMT activity, increased systemic exposure to levodopa, and reduced 3-OMD formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This was also evidenced by statistical significant decreases in both C max ( P = 0.0174) and AUC 3‐OMD ( P = 0.0330) values (Table 4). These results were similar to those reported in humans using nebicapone and Sinemet 100/25 or Sinemet CR 200/50 [6,12] . Another aspect that deserves to be underlined is that nebicapone appeared to anticipate the formation of 3‐OMD, as shown by the early detection of 3‐OMD in plasma (phase II and IV).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This was also evidenced by statistical significant decreases in both C max ( P = 0.0174) and AUC 3‐OMD ( P = 0.0330) values (Table 4). These results were similar to those reported in humans using nebicapone and Sinemet 100/25 or Sinemet CR 200/50 [6,12] . Another aspect that deserves to be underlined is that nebicapone appeared to anticipate the formation of 3‐OMD, as shown by the early detection of 3‐OMD in plasma (phase II and IV).…”
Section: Resultssupporting
confidence: 88%
“…Nebicapone increases the bioavailability of levodopa and reduces the formation of 3‐O‐methyldopa (3‐OMD) when administered concomitantly with levodopa/carbidopa 100/25 mg (Sinemet 100/25) or with controlled‐release levodopa/carbidopa 200/50 mg (Sinemet CR 200/50) [6,12] …”
Section: Introductionmentioning
confidence: 99%
“…Several studies with nebicapone in healthy subjects [9][10][11][12][13][14]28] and in PD patients [15], in which more than 180 subjects were exposed to different dosage regimens of nebicapone, did not raise any liver safety concerns. In a placebo-controlled study (submitted to publication) in which healthy subjects were administered a relatively high daily dose of nebicapone for 7 days, a clinically significant increase in ALT values was observed in 1 subject treated with nebicapone 6 × 100 mg/day and 1 subject treated with 6 × 200 mg/day, for 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Nebicapone is a new reversible and mainly peripherally acting COMT inhibitor currently being developed for use as an adjunct to levodopa/DDCI in the treatment of PD [9][10][11][12][13][14]. A previous study in 16 PD patients showed that multiple doses of 75 and 150 mg nebicapone inhibited COMT activity, increased the levodopa bioavailability, and were efficacious and well tolerated when administered concomitantly with standard release 100/25 mg levodopa/carbidopa [15].…”
Section: Introductionmentioning
confidence: 99%